Soft contact lens surface profile by atomic force microscopy - Giraldez, Maria J. (2010)
Purpose. This study was designed to qualitatively and quantitatively characterize the surface morphology of four unworn conventional hydrogel contact lenses (omafilcon, hioxifilcon, nelfilcon A, and ocufilcon B) and two silicone-hydrogel contact lenses (senofilcon A and comfilcon A) without surface treatment. Methods. Surface roughness was assessed using atomic force microscopy in Tapping ModeTM to determine the representative roughness parameters mean surface roughness (Ra), mean square roughness (Rms), kurtosis (Rku), and skewness (Rsk). To date, these last two parameters have not been used to characterize contact lens surfaces. Rku provides information on the distribution of spikes above and below the mean line, and Rsk provides information about the asymmetric roughness of surfaces. The surface topography of the lenses was also mapped in detail. Results. In all the lenses, higher Ra and Rms values were obtained when larger surface areas were examined. The daily replacement contact lenses (nelfilcon A and ocufilcon B) showed the highest Ra and Rms values but according to their Rku scores, their surface profiles were less spiky than the remaining lenses. On the contrary, the lowest Ra and Rms values were recorded for comfilcon A and omafilcon A, which also exhibited the spikiest surface profiles. All the materials except the hioxifilcon showed a predominance of peaks (Rsk) over troughs. Conclusions. The shape parameters Rku and Rsk are useful for characterizing contact lens surfaces, because they provide different yet complementary information to that offered by Ra and Rms. Precise knowledge of the shape profile of a contact lens surface will give an idea of its susceptibility to deposit formation or colonization by microorganisms.